Naturgenuss und Weltgemälde. Gedanken zu Humboldts Kosmos - Eberhard Knobloch (HiN - Alexander von Humboldt im Netz. Internationale Zeitschrift für Humboldt-Studien, 2004)
Article in German, Abstracts in English and German. Humboldt’s „Kosmos“ or „physical world description“ aimed at the same time at the outer and at the inner world. Corresponding to Horace’s famous dictum it was meant to be useful and to delight. Such a description was characterized by two notions, that is by force and by liberty. The paper deals with Humboldt’s conception of his work, with his notion of nature, taken from the elder Pliny. Again and again Humboldt named his famous model namely Laplace whose methodological principles coincided with his own convictions. The paper demonstrates that and how Humboldt was influenced by Herder without mentioning Goethe’s friend and explains Kant’s role in this context. The final aims of Humboldt’s conception of natural science were the laws of nature which connected natural phenomena with each other. Finally Humboldt’s high respect for mathematics is analysed.